The changing roles of graduate women in Tonga : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (Social Science) in social anthropology at Massey University - Kupu, Lesieli Ikatonga (Massey University, 1989)
This thesis examines the roles of graduate women in modern Tonga and how they differ from the women's traditional roles. A survey of a group of graduate women and how they perform at work, at home and in the community was undertaken. This was to investigate their own perceptions of the place graduate women have in their own society. Evidence from the study indicates that graduate women have changed in the ways they fulfil their roles. At work they are no longer confined to "women's work", but they are beginning to take up prominent positions in the office. This has had an impact on their relationships with their male superiors and both their male and female colleagues. At home, graduate women have become "providers" for their family, and that has given them a say in the family as a decision-making body. In church and community functions, there is a marked decrease in active participation but an increase with financial contributions. In conclusion, the graduate women know that their roles are changing. This change is determined by a combination of factors. While these factors liberate the graduate women from the pressure of social obligations, the same means of liberation have also isolated them from other social groups in Tongan society.
Keywords: Tonga; Women college graduates